2016
DOI: 10.7903/cmr.15752
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Contextualizing Board Structure on Firm Financial Performance in an Emerging Market

Abstract: The impact of the emerging markets context has been largely neglected in mainstream corporate governance research. The purpose of this paper is to conduct the first empirical study that investigates the relationship between board structure and firm financial performance through bundling theory with contextual considerations for economic, political, and social elements of the emerging Saudi Arabian market. This study uses archival data from a longitudinal sample of all listed firms in the Saudi market for years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Board size, board composition and ownership structure have garnered a significant amount of attention in their effects on a firm’s disclosure and performance (Migliardo and Forgione, 2018; Elmagrhi et al , 2018; Hanafi et al , 2018; Ali, 2018; Almadi, 2016; Haniffa and Cooke, 2002; Cheng and Courtenay, 2006; Ghazali, 2010; Hassan and Halbouni, 2013). Therefore, our study controls for these variables’ confounding influences on the dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Board size, board composition and ownership structure have garnered a significant amount of attention in their effects on a firm’s disclosure and performance (Migliardo and Forgione, 2018; Elmagrhi et al , 2018; Hanafi et al , 2018; Ali, 2018; Almadi, 2016; Haniffa and Cooke, 2002; Cheng and Courtenay, 2006; Ghazali, 2010; Hassan and Halbouni, 2013). Therefore, our study controls for these variables’ confounding influences on the dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Chancharat et al (2019) and Umrani et al (2017) found that board structure attributes have positively related to firm performance. According to Almadi (2016), optimising board member recognition through informal institutions determines the actual boardroom players who influence firm profitability. Businesses that have a larger board structure, more independent directors, executive directors, prevent CEO duality, have a CFO chair, hold regular meetings, and have an effective board can perform better and lead to the application of strong corporate governance principles (MCCG 2021).…”
Section: Board Structurementioning
confidence: 99%
“…The formal institutional dimension includes the political process from which the rules and regulations originate (Hillman & Keim, 1995) and the enforcement of the rules (Meyer et al, 2009). The informal institutional dimension includes acceptable behaviors, customs, and internalized beliefs of social actors, and both formal and informal institutional pressures may constrain strategic choice and behavior (Almadi, 2016;Hiatt & Park, 2013;Peng 2002Peng , 2003Peng , 2014.…”
Section: Institutional Theory and Nonprofitsmentioning
confidence: 99%
“…Institutional theory considers how societal norms, rules, and practices form institutional pressures and place pressure on organizations, shaping the way they operate within these societies along with the strategic options that are available to them (Almadi, 2016;Hitt, Ahlstrom, Dacin, Levitas, & Svobodina, 2004;Lu, Xu, & Liu, 2009;Meyer, Estrin, Bhaumik, & Peng, 2009;Ren & Jack, 2014). These pressures can be divided into formal and informal: the formal government regulatory context and the more informal aspect of culture and norms.…”
Section: Introductionmentioning
confidence: 99%